2022
DOI: 10.1007/s12070-022-03401-w
|View full text |Cite
|
Sign up to set email alerts
|

Anosmia—An Effect of COVID-19 Infection-Review

Abstract: The World Health Organization announced on March 11, 2020 that COVID-19 could become a pandemic. COVID-19 is a contagious disease caused by the coronavirus that causes severe acute respiratory syndrome (SARS-CoV-2). Viruses usually enter the body through the mouth or nose. The virus then enters the alveoli, which are small air sacs inside the lungs. Cough, fatigue, fever, shortness of breath or breathing difficulties, and loss of smell and taste are all symptoms of COVID-19. Anosmia, also known as smell blindn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…anosmia and olfactory symptoms in patients with CoVID-19 are considered to be related to inflammation and damage to the olfactory nerves or receptors. these symptoms can vary in severity and duration among individuals (25). the results of the present study demonstrated that 47 individuals (90.4%) in the CoVID-19 group were receiving cortisone-based treatment (table XI).…”
Section: Significancesupporting
confidence: 56%
See 3 more Smart Citations
“…anosmia and olfactory symptoms in patients with CoVID-19 are considered to be related to inflammation and damage to the olfactory nerves or receptors. these symptoms can vary in severity and duration among individuals (25). the results of the present study demonstrated that 47 individuals (90.4%) in the CoVID-19 group were receiving cortisone-based treatment (table XI).…”
Section: Significancesupporting
confidence: 56%
“…Anosmia and olfactory symptoms in patients with COVID-19 are considered to be related to inflammation and damage to the olfactory nerves or receptors. These symptoms can vary in severity and duration among individuals ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of COVID-19 on the lungs is caused by a complex molecular pathogenesis that involves interactions between the virus and the human respiratory system. The majority of COVID-19 patients experience mild flu-like symptoms, such as fever, cough, rhinorrhea, general malaise, and loss of taste and smell which are brought on by the virus [ 15 ]. However, a small percentage of individuals develop severe respiratory distress arising from the ensuing acute lung injury (ALI), such as pneumonia, which is typically accompanied by coagulopathy and can require mechanical ventilation in extreme cases.…”
Section: Common Pathological Features Between Covid-19 and Alzheimer’...mentioning
confidence: 99%